The mediation of labor satisfaction in the relationship of the leadership style and organizational commitment - Guerrero Bejarano, María Auxiliadora (2021)
The objective of this work was to determine the relationship between job leadership style and job satisfaction, and how this relationship affects organizational commitment; using the leadership theory of Bass and Avolio, through the MLQ questionnaire. The organizational commitment was measured with the tool generated from the Meyer and Allen theory and job satisfaction with the Paul Spector questionnaire. The study was outlined with the theoretical basis of the quantitative approach, deductive, cross-sectional method. Data collection was carried out through the survey with the respective questionnaire for each variable, the sampling was for convenience, and 386 people participated voluntarily. Data were analyzed with an SEM model. The results show that the data have a good fit according to the Chicuadrado test; in addition, convergent and divergent validity was performed. Therefore, in Ecuadorian reality it was shown that transformational leadership is related to job satisfaction (r = .55, p <0.05), while transactional leadership is negatively related to satisfaction (r = -. 154, p <0.05). However, transactional leadership is not